Strategy for Preserving Rare Collections Using the Preservation Pyramid Theory at the UPT Bung Hatta Proclamator Library - Nisa Nisa; Desriyeni Desriyeni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the high vulnerability of rare collections to physical, chemical, and biological deterioration, particularly in tropical environments with limited environmental control. Despite their substantial historical and cultural value, preservation strategies in specialized libraries remain insufficiently integrated and optimized. This study aims to analyze rare collection preservation strategies at the UPT Bung Hatta Proclamator Library based on the Preservation Pyramid Theory and to identify the supporting and inhibiting factors affecting their implementation. A qualitative approach with a case study design was employed. Six informants were purposively selected, comprising the head of preservation, preservation team members, a conservator, librarians, and a user. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that preservation strategies have been implemented across four levels: preventive conservation, passive conservation, active conservation, and restoration, with preventive conservation as the dominant strategy. These efforts include environmental control using dehumidifiers, silica gel, and thermohygrometers, as well as restricted access policies. However, several limitations remain, including budget constraints, suboptimal storage facilities, and inconsistent documentation practices. Active conservation and restoration have been relatively well implemented with support from trained conservators, although technical constraints persist. The study concludes that rare collection preservation at the UPT Bung Hatta Proclamator Library has been implemented but is not yet fully integrated across strategic and operational levels. Its contribution lies in demonstrating the relevance of the Preservation Pyramid Theory for evaluating rare collection management in specialized libraries and emphasizing the need for stronger institutional policies, preservation-standard facilities, and enhanced human resource capacity to ensure sustainable rare collection preservation.